A LONG WAY GONE – MEMOIRS OF A BOY SOLDIER/ISHMAEL BEAH - Van Zyl, Gerhard (Scientia Militaria - South African Journal of Military Studies, 2011)
The relevance of a book review of a fictional account of the life story of a child soldier in Sierra Leone for a journal such as Scientia Militaria is twofold: a) Truth (reality) remains stranger (more horrific) than fiction; b) Based on national foreign policy, the truth (realities) of Sierra Leone is by continental affiliation a South African reality, and by micro-affiliation an SANDF reality. This book challenges contemporary society, which is continuously bombarded and often jaded by faceless or nameless graphic news scenes. Those portions of society that remain blinded by prejudice and self-centred socio-political gaze to the severity of these scenes, are now confronted with a face and a name: Ishmael Beah. Physical combat methods to end human-on-human atrocities are welldocumented. These methods, augmented by root-level resistance and general human tenacity to overcome, often brought ends to what were at the height of their existence perceived as endless oppressive reigns of varied proportions (World War II, Apartheid, the Berlin Wall, Serbian rule, etc.).